Final analysis of the ALTTO trial: adjuvant trastuzumab in sequence or in combination with lapatinib in patients with HER2-positive early breast cancer [BIG 2-06/NCCTG N063D (Alliance)] - de, Azambuja, E (2024)
Background: Dual anti-human epidermal growth factor receptor 2 (HER2) blockade has improved the outcomes of patients with early and metastatic HER2-positive breast cancer. Here we present the final 10-year analysis of the ALTTO trial. Patients and methods: The ALTTO trial (NCT00490139) is a prospective randomized, phase III, open-label, multicenter study that investigated the role of adjuvant chemotherapy and trastuzumab alone, in combination or sequentially with lapatinib. The primary endpoint was disease-free survival (DFS) and secondary endpoints included overall survival (OS), time to distant recurrence and safety. Results: Overall, 6281 patients with HER2-positive early breast cancer were included in the final efficacy analysis in three treatment groups: trastuzumab (T), lapatinib + trastuzumab (L + T) and trastuzumab followed by lapatinib (T→L). Baseline characteristics were well balanced between groups. At a median follow-up of 9.8 years, the addition of lapatinib to trastuzumab and chemotherapy did not significantly improve DFS nor OS. The 10-year DFS was 77% in T, 79% in L + T and 79% in T→L, and the 10-year OS was 87%, 89% and 89%, respectively. The incidence of any cardiac event was low and similar in the three treatment groups. Conclusions: With a longer follow-up, no significant improvement was observed in DFS in patients treated with dual anti-HER2 blockade with lapatinib + trastuzumab compared to trastuzumab alone. The 10-year survival rates for the combination group are consistent with other studies that have explored dual anti-HER2 therapy.